Impact of Covid-19 Pandemic on Household Income: Results of a Survey of the Economically Active Population - Pinkovetskaia, Iuliia (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
The aim of the study is to assess the current impact of the Covid-19 pandemic on the level of household income in modern national economies according to data for 2020. The assessment of five indicators that characterize the opinions of adults living in different countries about a strong decrease, a small decrease, preservation, a small increase and a strong increase in their income in 2020 was considered. The initial data were the results of a survey of the economically active population in 43 countries, in the process of implementing the Global Entrepreneurship Monitoring project. The five indicators were evaluated using the density functions of the normal distribution. It is proved that for the majority (53%) of households, due to the pandemic, there was a decrease in household income. It shows the preservation of income in a significant (40%) number of households in the countries under consideration. It is shown that the increase in income in 2020 was observed only in a small number (less than 4%) of households. It is proved that the values of each of the five indicators under consideration had a significant differentiation by country. The results of our work have a certain theoretical and practical significance for governments and the economically active population. The methodological approach presented in the article can be used to assess the impact of the Covid-19 pandemic on household income in 2021.